Development of a Standing Equine Leg CT (slCT). (1st March 2022) - Moliner, L.; Bolas, N.; Pallas, E.; Rodríguez-Álvarez, M.J.; Benlloch, J.M.
Abstract: All horse ridden disciplines result in stresses to both bony and soft tissue structures. Many competitive horses experience extreme forces on the structures of the lower limb whilst executing transitions such as a tight turns or rapid acceleration. Lameness subsequent to distal limb injury is common to both the performance and pleasure horse, resulting in time out of ridden work at best or career ending at worst. In this context, Hallmarq Veterinary Imaging Ltd (a company dedicated to veterinary imaging) and the Institute of Instrumentation for Molecular Imaging (i3M) established a collaboration in order to develop a CT prototype device for the examination of horse limbs. The Standing Equine Leg CT (slCT) is an additional tool for equine veterinarians to fully evaluate and diagnose lameness, fracture and disease in the equine distal limb.